Port Services and Perceived Price Through Customer Satisfaction Implications for Customer Loyalty Freight Forwarding Company at Tanjung Priok Port, Jakarta - Arifiani, Librita; Umbara, Oky Nurandana; Thamrin, Muhammad; Sonny, Imam; Octora, Theresye Yoanyta; Kuncoro, Yahya (Institut Transportasi dan Logistik Trisakti, 2025)
PT. MAL one of the container terminals at Tanjung Priok Port has experienced problems related to customer loyalty. Container terminals and the emergence of new competitors are competing to improve service quality and offer perceived prices to satisfy their customers where the level of perceived satisfaction is veritably important demand to get loyal customers. The objective of this study is to analyze the direct influence of port service quality and perceived price on customer loyalty and the indirect effect of customer satisfaction on customer loyalty. The analytical method this study uses is the partial least squares method of the structural equation model with sampling technique. using a total sampling of 60 respondents representing export/import companies, shipping companies or agents, forwarding companies, and consignees. The results of this study are that the quality of port services and perceived price have a direct positive and significant effect with the endogenous variable of customer loyalty and an indirect effect through the intervening variable of customer satisfaction